2014
DOI: 10.1097/qai.0000000000000135
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacokinetics and Acceptability of Lopinavir/Ritonavir Minitab Sprinkles, Tablets, and Syrups in African HIV-Infected Children

Abstract: LPV/r exposure from minitabs was comparable with syrup, but lower than tablets, with no significant differences in subtherapeutic concentrations. Minitabs were more acceptable than syrups for younger children, but older children preferred tablets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 8 publications
2
61
1
Order By: Relevance
“…Recently approved integrase inhibitors and protease inhibitors with better safety profiles and dosage intervals are competing as preferred first-line regimens. A summary of recently approved antiretroviral drugs is provided in Table 2 [40][41][42][43][44][45][46][47][48][49][50][51][52][53]. Tenofovir has been licensed for children >2 years of age at 8 mg/kg daily.…”
Section: Retention In Care and Antiretroviral Therapymentioning
confidence: 99%
“…Recently approved integrase inhibitors and protease inhibitors with better safety profiles and dosage intervals are competing as preferred first-line regimens. A summary of recently approved antiretroviral drugs is provided in Table 2 [40][41][42][43][44][45][46][47][48][49][50][51][52][53]. Tenofovir has been licensed for children >2 years of age at 8 mg/kg daily.…”
Section: Retention In Care and Antiretroviral Therapymentioning
confidence: 99%
“…As part of a recent clinical study, Musiime et al reported that older children aged 4 to 13 years old who were able to swallow tablets found these more acceptable than 265 mini-tablets that were administered with food (Musiime et al, 2014). Problems with taste and swallowing difficulties were reported by 50% and 13% of the cohort respectively for the mini-tablet product, while neither problem was reported with tablets.…”
Section: Novel Dosage Formsmentioning
confidence: 99%
“…Of note, a higher percentage of missed medication doses was estimated in the LPV/r group than the 3TC group (26% for the LPV/r group versus 11% for the 3TC group). This may be explained, in part, by the fact that the LPV/r syrup formulation is often described to have an unpleasant taste (16). After exclusion of the data for samples from infants that may Our study shows that none of the HIV-exposed infants whose values were below the therapeutic pharmacokinetic target acquired HIV infection during the trial period.…”
Section: Discussionmentioning
confidence: 88%